103k views
0 votes
Jason knows that the equation to calculate the period of a simple pendulum is , where T is the period, L is the length of the rod, and g is the acceleration due to gravity. He also knows that the frequency (f) of the pendulum is the reciprocal of its period. How can he express L in terms of g and f?

1 Answer

0 votes

Answer:


L=(g)/(4\pi^2 f^2)

Explanation:

The equation to calculate the period of a simple pendulum is:
T=2\pi \sqrt{(L)/(g) }

Where:

  • T is the period
  • L is the length of the rod; and
  • g is the acceleration due to gravity.

Likewise, Frequency (f) of the pendulum
f=(1)/(T) therefore
T=(1)/(f)

We want to express L in terms of g and f.

From


T=2\pi \sqrt{(L)/(g) }


T=(1)/(f)


(1)/(f)=2\pi \sqrt{(L)/(g) }\\$Divide both sides by 2\pi\\(1)/(2\pi f)=\sqrt{(L)/(g) }\\$Square both sides\\\left((1)/(2\pi f)\right)^2=(L)/(g)


(1)/(4\pi^2 f^2)=(L)/(g) \\$Multiply both sides by g\\Therefore: L=(g)/(4\pi^2 f^2)

User Criz
by
5.3k points